Actinomadura Species: Laboratory Maintenance and Ribosome Engineering. Issue 1 (6th February 2017) - Dhakal, Dipesh; Chung, Nguyen Thanh; Rayamajhi, Vijay; Sohng, Jae Kyung
Abstract: Actinomadura spp. are aerobic, Gram‐positive, catalase‐positive, non‐acid fast, non‐motile actinomycetes. Some species of Actinomadura are associated with opportunistic infections in humans. However, many bioactive compounds with pharmaceutical applications can be isolated from various Actinomadura spp. This unit includes general protocols for the laboratory maintenance of Actinomadura spp., including growth in liquid medium, growth on solid agar, long‐term storage, and generation of a higher producing strain by ribosome engineering. Actinomadura hibisca P157‐2 is used as a prototype for explaining the considerations for efficient laboratory maintenance of Actinomadura spp. © 2017 by John Wiley & Sons, Inc.